Profil Kenakalan Remaja Siswa Kelas VIII A SMP Negeri 16 Kupang dan Implikasinya bagi Bimbingan Pribadi Sosial - Hendriana Hingi Liwun; Rosa M Bulor; Kristinus Sembiring (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study originated from the high rate of delinquent behavior among adolescents in schools, which risks disrupting their personal and social development. The purpose of this study is to describe the characteristics of adolescent delinquency and analyze its impact on personal and social guidance programs at UPTD SMP Negeri 16 Kupang for the 2024/2025 academic year. The method used in this study was quantitative descriptive, taking a full sample of 28 students from class VIII A. The sampling technique used was saturated sampling with a measurement tool in the form of a questionnaire on juvenile delinquency. The questionnaire used a Likert scale with four answer choices and had been tested for validity through Pearson's Product Moment correlation and reliability. Based on data analysis, the results of this study show that the average juvenile delinquency score reached 154.21 with a standard deviation of 14.66 and a standard error of 2.77. At a significance level of 5% (z = 1.96), the confidence interval was in the range of 148.78 to 159.64. Therefore, the level of juvenile delinquency among students in class VIII A of UPTD SMP Negeri 16 Kupang is classified as very high, covering aspects of delinquency that cause physical harm to others, delinquency that causes material loss, social delinquency that does not cause harm, and delinquency that violates norms. Factors influencing this behavior originate from both internal and external sources, such as family, school, community, and technological influences. The results of this study emphasize the importance of implementing personal and social guidance programs in schools to improve self-control, social skills, communication, and responsibility in adolescents. It is hoped that the results of this study can serve as a guide for guidance and counseling teachers in designing more effective services to reduce deviant behavior and create a better learning environment.